Rosai-Dorfman disease in a child with involvement of extra-nodal wrist joint - Das, Rajjyoti; Sharma, Jagannath Dev; Baishya, Nizara; Krishnatreya, Manigreeva; Choudhary, Binoy Kumar; Kataki, Amal Chandra (International Journal of Research in Medical Sciences, 2017)
Rosai-Dorfman Disease (RDD) is a benign condition primarily affecting the lymph nodes. The term sinus histiocytosis with massive lymphadenopathy was first used. There may be extra-nodal presentation of RDD with or without constitutional symptoms. A 10-year-old boy presented with massive bilateral cervical lymphadenopathy which mimicked the diagnosis of lymphoma. We describe here a case of RDD in a child with extra-nodal bone involvement of the wrist joint, its diagnosis by histopathological examination supported by immunohistochemistry and consequent initial management.